Implementasi Manajemen Berbasis Sekolah (MBS) Dalam Peningkatan Mutu Pendidikan di Madrasah - Miftahul Jannah; Ulfa Dwiyanti Sunardi; Mardiatul Husnah; Ibnu Ramdan Syafaat; Muhammad Patra (IAIN Parepare, 2025)
This study examines the implementation of School-Based Management (SBM) in improving the quality of education in madrasahs. SBM provides autonomy to madrasahs in managing resources, decision-making, and actively involving all stakeholders. A descriptive qualitative approach using literature review was employed, with literature selected purposively based on relevance, credibility, and recency. Findings indicate that SBM enhances effectiveness, efficiency, and community participation, while challenges include limited budgets, human resource capacity, and cultural resistance. Strengthening strategies involve continuous training, technology utilization, transparency improvement, and consistent policy support. Systematic and coordinated implementation of SBM can foster autonomous, professional, and high-performing madrasahs.